2009
DOI: 10.1088/0953-4075/42/21/215506
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of entanglement amplification in a nondegenerate three-level cascade laser employing various inseparability criteria

Abstract: A detailed comparison among the exhibited nature of entanglement of the cavity radiation of the nondegenerate three-level cascade laser when different inseparability criteria are employed is presented. Although the achievable degree of entanglement is generally found to vary with the applied inseparability criteria, there are cases for which more than two of the applied criteria lead to a significant degree of entanglement for certain parameters. Particularly, the procedures following from the criterion of Dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 38 publications
5
38
2
Order By: Relevance
“…The nonclassical correlation in this system seems to repeat the absence of the bipartite entanglement in a three-level cascade system when the lower and the upper energy levels are prepared in a maximum coherent superposition [32].…”
Section: Demonstration Of the Tripartite Entanglementmentioning
confidence: 60%
See 1 more Smart Citation
“…The nonclassical correlation in this system seems to repeat the absence of the bipartite entanglement in a three-level cascade system when the lower and the upper energy levels are prepared in a maximum coherent superposition [32].…”
Section: Demonstration Of the Tripartite Entanglementmentioning
confidence: 60%
“…It can be asserted that initially preparing atoms in a certain coherent superposition and then allowing them to follow realistic spontaneous transition roots can yield a strongly entangled light [31][32][33]. Taking this as a motivation, the Y-shaped four-level atomic system initially prepared in a coherent superposition of the energy levels between which a direct electric dipole transition is forbidden would be considered.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…It has been shown that the Hillery-Zubairy criterion is another equivalent entanglement criterion with Cauchy-Stewart inequality when the inter-atomic interaction is not taken into account [22]. This is contrary to the other criterion and the result reported in in which the driven atomic coherence is used.…”
Section: Hillery-zubairy Criterionmentioning
confidence: 79%
“…A pair of particles is said to be entangled in quantum theory, if its states cannot be expressed as a product of the states of its individual constituents. (22) in which P j > 0 and Σ j P j = 1 is set to ensure normalization of the combined density of state.…”
Section: Continous Variable Entanglement Criteriamentioning
confidence: 99%
“…Previous study shows that the nature of the predicted degree of entanglement by the two criteria for a similar system when Ω = 0, θ = 0 and γ = Γ has the same form except near η = 0 where significant disparity was observed at steady state [20]. The main aim here is shifted to the study of the time evolution of the entanglement upon using γ/Γ and θ as a probe.…”
Section: A Duan-giedke-cirac-zoller Criteriamentioning
confidence: 94%